2022
DOI: 10.1002/essoar.10512288.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Mesoscale Cloud Morphology in the Shortwave Cloud Feedback

Abstract: This a preprint and has not been peer reviewed. Data may be preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…I. L. McCoy et al. (2022) have shown that environmentally driven transitions between Sc cloud morphologies coincide with variations in thin cloud features, which as shown here, control the magnitude of the bias in β . Future changes in the frequency of occurrence of Sc cloud morphologies could therefore influence the magnitude of RF aci .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…I. L. McCoy et al. (2022) have shown that environmentally driven transitions between Sc cloud morphologies coincide with variations in thin cloud features, which as shown here, control the magnitude of the bias in β . Future changes in the frequency of occurrence of Sc cloud morphologies could therefore influence the magnitude of RF aci .…”
Section: Discussionsupporting
confidence: 63%
“…Future changes in the frequency of occurrence of Sc cloud morphologies could therefore influence the magnitude of RF aci . Such changes could be attributed to various factors, including cloud feedbacks (I. L. McCoy et al., 2022), changes in cloud thickness resulting from rising CO 2 concentrations (Schneider et al., 2019), and changes in aerosol levels that can influence Sc transitions (Goren et al., 2019, 2022). Our results also show that for a given cloud albedo, β tends to be larger under more heterogeneous conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of future climate, MCC morphology has been shown to have a nontrivial contribution (∼0.07 W m −2 K −1 ) to the shortwave cloud feedback, based on the environmental dependence of MCC morphology in the current climate (McCoy et al., 2022). This contribution may vary as aerosol indirect forcing changes in a future warmer world, yet the effect of anthropogenic atmospheric aerosol on MCC morphology remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%